2005
DOI: 10.1073/pnas.0409863102
|View full text |Cite
|
Sign up to set email alerts
|

HEXIM1 forms a transcriptionally abortive complex with glucocorticoid receptor without involving 7SK RNA and positive transcription elongation factor b

Abstract: The HEXIM1 protein has been shown to form a protein-RNA complex composed of 7SK small nuclear RNA and positive transcription elongation factor b (P-TEFb), which is composed of cyclindependent kinase 9 (CDK9) and cyclin T1, and to inhibit the kinase activity of CDK9, thereby suppressing RNA polymerase II-dependent transcriptional elongation. Here, we biochemically demonstrate that HEXIM1 forms a distinct complex with glucocorticoid receptor (GR) without RNA, CDK9, or cyclin T1. HEXIM1, through its arginine-rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…Our observation extends already established mechanisms of repression by Hexim1, where its BR binds transcriptional activators and blocks their activity (20)(21)(22). In addition, our data reveal that Hexim1 can inhibit transcriptional activators in trans, by decoying P-TEFb away from them, which presents a conceptually previously undescribed mechanism for the inhibition of transcription by Hexim1.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Our observation extends already established mechanisms of repression by Hexim1, where its BR binds transcriptional activators and blocks their activity (20)(21)(22). In addition, our data reveal that Hexim1 can inhibit transcriptional activators in trans, by decoying P-TEFb away from them, which presents a conceptually previously undescribed mechanism for the inhibition of transcription by Hexim1.…”
Section: Discussionsupporting
confidence: 60%
“…Because BR in Hexim1 is necessary for the inhibition of p65, ER␣, and glucocorticoid receptors, we were interested in whether the same is true for CIITA (20)(21)(22). Surprisingly, the mutant f:NLS.Hex1(181-359) protein lacking the BR still inhibited the activity of CIITA to the same extent as the mutant f:Hex1 (150-359) protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a process may result in the cooperative formation of P-TEFb⅐HEXIM⅐7SK complexes. It has recently been reported that HEXIM1 associates steroid hormone receptors (30,31). It will be challenging to examine whether binding of one HEXIM1 subunit to this transcription factor can help recruit P-TEFb bound to the other HEXIM1 subunit onto steroid hormone-responsive promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Both ER␣ and GR have been independently identified as HEXIM1-associated factors. In the case of GR, it forms a separate complex with HEXIM1 that is distinct from the HEXIM1-7SK-P-TEFb complex (87). Overexpression of HEXIM1 decreases liganddependent association between GR and the p160 coactivator transcriptional intermediary factor 2, resulting in suppression of glucocorticoid-responsive gene activation (87).…”
Section: Association Of Hexim1 With Nuclear Hormone Receptorsmentioning
confidence: 99%